Analisis Faktor-Faktor Yang Menentukan Preferensi Masyarakat Kota Medan Terhadap Pembayaran Non Tunai. - Rangga Salam (AGHNIYA : Jurnal Ekonomi Islam, 2021)
This study aims to determine whether the Efficiency, Obligation, Security, Convenience and Discount affect people's preferences for non-cash payments in Medan City. This type of research is quantitative analysis, this research is the result of data collection which is analyzed in order to get a clear picture of the object under study in the city of Medan which includes workers ranging from employees, business actors as well as students as well as people who are considered related in this study. The choice of this location is related to researchers who are domiciled in the area around Medan. Of the five variables that have the greatest influence is the security variable with Beta Coefficient of 0.442, therefore all relevant stakeholders should be more active in introducing the value value of non-cash payments in order to increase public confidence in making non-cash payment transactions so that the economy of the sector finance in the city of Medan is increasing.